Síntese e caracterização de pós e filmes finos de SrSn1-xTixO3 - Oliveira, André Luiz Menezes de (2013)
Strontium stannate (SrSnO3) and titanate (SrTiO3) are perovskite type oxides that have orthorhombic (Pbnm) and cubic (Pm3m) structures, respectively. These materials have received much attention due to their interesting physical and chemical characteristics, leading to a variety of technological applications. In this sense, these two materials were combined to each other in order to obtain powders and thin films of a solid solution, SrSn1-xTixO3. In relation to the powders, this solid solution presented successive phase transitions ranging from orthorhombic and tetragonal structures to a cubic one with increasing of Ti4+ amount in the composition. These transitions were observed by XRD Rietveld refinement of the samples and confirmed by Raman spectroscopy. The different crystalline structures of the compositions within the solid solution led to different photoluminescent properties in the visible spectrum varying the range of emission, moving from a lower energy region to a higher one with increasing of Ti4+ in the structure (from orthorhombic (SrSnO3), tetragonal (SrSn0.75Ti0.25O3) to cubic (SrSn0.50Ti0.50O3 ; SrSn0.25Ti0.75O3 and SrTiO3). These emissions were probably favored by specific defects created inside the band gap of these materials. On the other hand, the thin films of this system showed different growth orientations that are associated to the crystalline nature of the substrates, the composition of the thin films and the deposition method (Chemical Solution Deposition - CSD - and Pulsed Laser Deposition - PLD). The films deposited on silica substrate were polycrystalline (random growth of the crystallites), whereas the films deposited on sapphire-R (Al2O3-012) were also polycrystalline, with a preferred orientation (h00) for the films deposited by PLD (textured growth), except SrTiO3 which was rotated 45° epitaxially in the sapphire plane. On the contrary, all of the films deposited on LAO (LaAlO3-100) had an (h00) epitaxial growth. In addition to that, the morphological characteristics and photocatalytic properties were strongly influenced also by the same parameters described above. Regarding the photocatalytic efficiency of the films, those obtained by CSD were more efficient than the ones obtained by PLD. Moreover, the films with Sn4+ richer compositions were the most active in the photodegradation of the azo dye Remazol yellow gold, reaching a maximum efficiency with the polycrystalline SrSnO3 thin film obtained by CSD whose degradation and decolorization percentage were 55 and 90 %, respectively. The type of orientation of the SrSnO3 films showed also a strong influence on the photodegradation of the dye. The polycrystalline films with a random orientation obtained on silica were more efficient than the textured films and these ones were more than the epitaxial films